The Role Of Financial Education In Improving Student Financial Management - Sulikah Sulikah; Sulistyani Sulistyani; Rendika Valery (International Journal of Economics and Management Sciences, 2024)
The research aims to analyze financial management problems faced by students and analyze the role of financial education in improving financial management. This research was conducted using a qualitative approach to the literature study method. carried out by collecting secondary research data from various published research articles and those contained in scientific journals, documents, reference sources that are in accordance with the topic of the role of financial education in improving student financial management. The research results show that students' financial management still needs to be improved and financial education, both formal and informal, is proven to be able to contribute to improving this ability